2022
DOI: 10.1080/13814788.2022.2057947
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an intensive care unit admission on the health status of relatives of intensive care survivors: A prospective cohort study in primary care

Abstract: Background Relatives of intensive care unit (ICU) survivors may suffer from various symptoms after ICU admittance of their relative, known as post-intensive care syndrome-family (PICS-F). Studies regarding PICS-F have been performed but its impact in primary care is unknown. Objectives To explore health problems of relatives of ICU survivors in primary care. Methods This is an exploratory prospective cohort study in which we combined data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…After three months, patients admitted to the ICU remain to have significant more GP consultations compared to the matched reference patients. A recent study with similar methods and the same database origin found that relatives of patients admitted to the ICU also present more morbidity in primary care compared to relatives of chronically ill patients after ICU admission, making the health aspects of critical illness far more wide-ranging than the diagnosis of ICU admission itself [ 34 ]. Additionally, a remarkable finding was that patients admitted to the ICU also encountered more new disease-episodes and GP contacts 1 year before ICU admission compared to patients without ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…After three months, patients admitted to the ICU remain to have significant more GP consultations compared to the matched reference patients. A recent study with similar methods and the same database origin found that relatives of patients admitted to the ICU also present more morbidity in primary care compared to relatives of chronically ill patients after ICU admission, making the health aspects of critical illness far more wide-ranging than the diagnosis of ICU admission itself [ 34 ]. Additionally, a remarkable finding was that patients admitted to the ICU also encountered more new disease-episodes and GP contacts 1 year before ICU admission compared to patients without ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Dutch study found that relatives of former ICU patients had a higher number of new episodes of primary care 2-5 years after ICU discharge, but not in the first year. They suggested that relatives might prioritize the health of the former ICU patient over their own in the first year after ICU discharge and develop a broad range of symptoms and diseases including psychologic morbidity more than 1 year after discharge (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, measurement of mental health symptoms among relatives only after 3 months may not have been sufficient, as patients’ rehabilitation trajectories vary. Similar studies collected longitudinal data before admission, as the mental health status of relatives before ICU admission may be an important predictor of mental health outcomes of relatives after the patient’s ICU stay ( 37 ) and following admission ( 18 , 38 , 39 ). Furthermore, as shown in this Dutch study, facilitating the process of participation was shown to increase the odds of a neutral to positive attitude toward participation, which probably will facilitate participation in daily ICU practice.…”
Section: Strengths and Limitationsmentioning
confidence: 99%